1977
DOI: 10.1136/bjo.61.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Aphakic macular oedema following prosthetic lens implantation.

Abstract: SUMMARY Fluorescein angiography of the iris was performed on patients with plastic lens implants with cystoid oedema of the macula, and the nature of the vascular changes was compared with controls provided by patients who did not have macular disease. Densitometry was used to quantitate leakage of fluorescein dye into the anterior chamber in residual angiograms 5 minutes after injection. Cystoid oedema was associated with marked increase in vascular permeability of the iris in the patients with implants, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This finding was also noted in the treated group. This result agrees with that of Easty et al [12], who used den sitometry. The above results do suggest, as Miyake described, that prostaglandins or other indomethacin-sensitive factors which are produced by surgical stimulation are associated with the onset of CME.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding was also noted in the treated group. This result agrees with that of Easty et al [12], who used den sitometry. The above results do suggest, as Miyake described, that prostaglandins or other indomethacin-sensitive factors which are produced by surgical stimulation are associated with the onset of CME.…”
Section: Discussionsupporting
confidence: 83%
“…It is also possible to attribute vasculitis of the entire ocular tissue of a CME patient, which Mar lin et al [13] found on histopathological specimens, to prostaglandins. Increasing ac tivities of these factors have been actually observed by measurements of prostaglandin E and F2a in the aqueous humor, preoperatively, and 1 week after operation [14], Easty et al [12] did not observe the increase of prostaglandins El and E2 from chronic CME patients, but the number of his cases was small. ///// [ 14], followed by many au thors [15], performed anterior vitrectomy for the removal of vitreous-surgical wound ad hesions in patients with CME, and in general they produced a marked improvement.…”
Section: Discussionmentioning
confidence: 99%
“…According to Easty et al (1977) examination by fluorescein angiography, in the absence of cystoid macular oedema, showed no evidence of vascular disturbance in eyes with intraocular lens implants. Ellingson ( 1978) described the UGH-syndrome with severe vascular complications.…”
mentioning
confidence: 94%
“…Post-operatively both pupillary margin and radial vessel will leak dye, the same finding will be noticed whether an intraocular lens has been inserted or not. There is no difference in the recovery time (Easty et al 1977).…”
mentioning
confidence: 96%
“…Prostalandins have the following effects upon the eye: miosis, rise of intraocular pressure, vasodilation in iris and ciliary body, breakdown of blood-aqueous barrier and cystoid macular edema (Cole and Unger, 1973;Easty et al, 1977;Neufeld and Sears, 1973;Podos and Becker, 1976;Unger et al, 1975). Indomethacin, belonging to the group of prostaglandin inhibitors, is claimed to diminish these effects after the posttraumatic (surgical) release of prostaglandin E and F2a (Bhattacherjee and Eakins, 1974;Eakins, 1977;Katz, 1981).…”
Section: Introductionmentioning
confidence: 99%